2019
DOI: 10.3357/amhp.5316.2019
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Assessment in Pilots

Abstract: BACKGROUND: For over 30 yr the global medical community has attempted to define the acceptable cardiovascular risk in pilots. This challenge is compounded by the ever-changing technological and medical landscape of air travel. We aimed to review the existing literature on estimating the risk of pilot cardiovascular incapacitation and determine if the current guidelines are founded in the best available evidence.METHODS: A detailed review of the guidelines and literature that supports them was completed. Relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…By focusing on updated trends, potential risk factors, and preventive measures, we aim to enhance aviation safety and safeguard the lives of those who navigate the skies. The findings of this review will have important implications for aviation regulatory bodies, airlines, and healthcare providers involved in the care of pilots (Mulloy et al, 2019) (20).…”
Section: Trends In Sudden Cardiacmentioning
confidence: 98%
See 1 more Smart Citation
“…By focusing on updated trends, potential risk factors, and preventive measures, we aim to enhance aviation safety and safeguard the lives of those who navigate the skies. The findings of this review will have important implications for aviation regulatory bodies, airlines, and healthcare providers involved in the care of pilots (Mulloy et al, 2019) (20).…”
Section: Trends In Sudden Cardiacmentioning
confidence: 98%
“…Regular cardiovascular risk assessment, including electrocardiography (ECG) and echocardiography, was found to be effective in identifying pilots at increased risk of SCD (20). Pilots who underwent regular cardiovascular risk assessment had a 40% lower risk of SCD compared to those who did not (RR: 0.6, 95% CI: 0.4-0.9) (19).…”
Section: Effectiveness Of Preventive Measures For Scd In Pilotsmentioning
confidence: 99%
“…For many years the “1% rule”, which states that no pilot should have an annual risk of cardiovascular incapacitation exceeding 1%, has served as a possible standard and is endorsed as the threshold of choice by the International Civil Aviation Organization (ICAO), but the methods of determining the risk to an individual pilot vary by jurisdiction [ 32 ]. The Framingham risk score (FRS) is a common and simple tool used for predicting of the risk of CVD development in next 10 years based on data related to age, gender, total cholesterol, status of diabetes, systolic blood pressure, high-density lipoprotein cholesterol (HDL), and tobacco smoking [ 3 ].…”
Section: Cvds Risk Scoresmentioning
confidence: 99%
“…This framework can be applied to a wide variety of clinical situations [ 37 ]. Mulloy and Wielgosz recently proposed the acceptable annual risk formula, which takes into consideration the unique variables inherent in flight for setting CVD risk in commercial pilots [ 32 ]. Moreover, Holdsworth et al proposed a three-dimensional (3D) risk matrix for practical decision making, where the acceptable clinical event rate is very low, to be used within high-hazard occupational medicine.…”
Section: Cvds Risk Scoresmentioning
confidence: 99%
“…Over the past years there have been several reports concerning civil pilots dead during flight due to serious cardiovascular events [1]. About that, in a group of pilots which were several months banned to fly since covid-19 lockdown and which simulated manoeuvres to takeoff, flying in route and landing, a previous study showed that in route mean arterial blood pressure (MAP) stayed at a mean value of about 104 Torr or 12% higher than expected [2].…”
Section: Introductionmentioning
confidence: 99%